PENGARUH KECERDASAN SPIRITUAL DAN GAYA HIDUP HEDONISME TERHADAP MANAJEMEN KEUANGAN PRIBADI MAHASISWA (STUDI KASUS MAHASISWA UNISAN SIDRAP) - Hesti Pujiastuti; Romy Nugraha JS; Jumriah Basri (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2024)
This research aims to: 1) determine the influence of spiritual intelligence partially on students personal financial management, 2) determine the influence of a hedonistic lifestyle partially on students personal financial management, and 3) determine the influence of spiritual intelligence and a hedonistic lifestyle simultaneously on financial management student personality. The type of research used is descriptive quantitative methods and causal relationships. With a population of 534 students, the sample in this study was 84 because this research is population research. Meanwhile, the type of data used is primary and secondary data. With data collection techniques using observation, interviews, questionnaires and documentation. The data analysis techniques used are: Data quality testing, classical assumptions, multiple regression analysis, and hypothesis testing. From the results of the research conducted, it can be concluded that there is an influence between spiritual intelligence and a hedonistic lifestyle (simultaneous test) on the personal financial management of students at Ichsan Sidenreng Rappang University. There is an influence of spiritual intelligence (partial test) on the personal financial management of management concentration students at Ichsan University. sidenreng rappang, the hedonistic lifestyle has no effect (partial test) on the personal financial management of Ichsan Sidenreng Rappang University students, and the influence of spiritual intelligence and the hedonistic lifestyle (simultaneous test) on the personal financial management of Ichsan Sidenreng Rappang University students. Keywords: Spiritual Intelligence, Hedonistic Lifestyle, Financial Management.